2016
DOI: 10.1111/codi.13429
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical prehabilitation in elderly patients undergoing colorectal surgery: a systematic review

Abstract: Prehabilitation is a possible means of enhancing the physical condition of patients preoperatively. The quality of studies in older patients undergoing colorectal surgery is poor, despite the increase in elderly people with colorectal cancer. Defining specific patient groups at risk and standardizing the outcome are essential for improving the results of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
118
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 57 publications
1
118
0
2
Order By: Relevance
“…Further-more, performing laparoscopic cholecystectomy on elderly patients has resulted in increased postoperative complications such as increased morbidity, biliary tract disease, and longer hospital stays 7 . These severe postoperative outcomes have been attributed to the lack of muscle strength and poor physical condition associated with the older patient population 7,8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further-more, performing laparoscopic cholecystectomy on elderly patients has resulted in increased postoperative complications such as increased morbidity, biliary tract disease, and longer hospital stays 7 . These severe postoperative outcomes have been attributed to the lack of muscle strength and poor physical condition associated with the older patient population 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Further-more, performing laparoscopic cholecystectomy on elderly patients has resulted in increased postoperative complications such as increased morbidity, biliary tract disease, and longer hospital stays 7 . These severe postoperative outcomes have been attributed to the lack of muscle strength and poor physical condition associated with the older patient population 7,8 . Though studies have found that laparoscopic cholecystectomy may cause less post-operative complications in general, it is still linked to longer operation time, pro-longed hospital stay, and higher morbidity in geriatric patients compared to the younger ones 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In a recent study of Barberan-Garcia et al in high-risk patients who underwent elective major abdominal surgery, exercise prehabilitation not only improved preoperative aerobic fitness, but also resulted in a 51% reduction in postoperative complications compared to the usual care group. [8][9][10][11][12] Most preoperative training programs were carried out under supervision in an outpatient clinic; however, a personalized exercise program in a home-based setting might enhance the participation rate, motivation, and adherence of (high-risk) patients, and has proven to be the preferred method for a prehabilitation program. 11,13,14 Although several studies investigated the effects of exercise prehabilitation in liver and/or pancreatic resection and reported positive effects on physical fitness and postoperative morbidity, there is limited evidence addressing the feasibility and effectiveness of supervised home-based prehabilitation in these populations.…”
Section: Introductionmentioning
confidence: 99%